Planificación familiar en la Guerra Fría chilena: política sanitaria y de cooperación internacional, 1960-1973 - Maria Soledad Zárate Campos; Maricela Gonzáles Moya (Historia Crítica, 2015)
This article seeks to document the links between the Chilean Family Planning Program and organizations such as the Population Council, the Rockefeller Foundation, the International Planned Parenthood Federation and the UN between 1960 and 1973. Within the framework of the population policies imposed by the Cold War, it analyzes the trajectory of the Chilean medical community, which, by sharing in the ideological guidelines of the international agencies, understood said relationship more as an efficient instrument for limiting high abortion rates than as means to significantly reduce population growth.